Anatomy and physiology of the nutritional system. (August 2019) - Cinti, Saverio
Abstract: The organisms of mammals are composed of organs cooperating as systems that are organized to perform functions which allow the survival of the individual and maintenance of the species. Thus, to reach the main goals of these functions we need systems that ensure nutrient uptake and distribution, thermogenesis, oxygen uptake and distribution, the discharge of toxic internal by-products, the defense from internal and external pathogens, gamete fertilization, and the fine-tuning of the activity of all the tissues composing the organs. Most of these activities also require interactions with the internal and external environment. The latter function is served by the nervous system and the others by the cardiovascular, respiratory, excretory, immune, reproductive and endocrine systems. Nutrient intake and distribution and thermoregulation are realized by the collaborative work of the adipose and the digestive organs. In this review I will outline data on adipose tissue anatomy and function which have been collected during the past 40 years. They provide a convergent body of evidence toward a new concept regarding the collaborative work between the adipose organ and the organs of the gastrointestinal tract, which constitute a system ensuring nutrient search, intake and distribution to the organism. Furthermore, the same system also seems to enable nutrient distribution to the offspring to ensure not only short-term but also long-term homeostasis. Graphical abstract: Arrows pointing to the brain indicate converging hormonal influences inducing a behavior that ensures survival (short-term homeostasis). Arrows pointing toward one another indicate reciprocal functional influences directed at ensuring functional collaboration to absorb (digestive organs) and store nutrients, whose aim is to support the organism (white adipocytes) and the offspring (pink adipocytes). The latter function ensures long-term homeostasis (species survival). Divergent arrows indicate system collaboration for thermogenesis, which also plays a role in meal interruption, especially in newborns.Image 1